2017
DOI: 10.1589/jpts.29.85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diaphragm breathing exercise and feedback breathing exercise on pulmonary function in healthy adults

Abstract: [Purpose] The present study investigated effects of diaphragm breathing exercise and feedback breathing exercise on respiratory function. [Subjects and Methods] Thirty-one subjects were randomly assigned to two groups; the feedback breathing exercise group and the maneuver-diaphragm exercise group. The feedback breathing exercise group was asked to breathe with feedback breathing device, and the maneuver-diaphragm exercise group was asked to perform diaphragm respiration. Respiratory function was evaluated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Han & Ha (2015) reported an increase in the maximum voluntary ventilation from 84.88 L to 112.62 L in reinforcement of the pelvic floor through pelvic floor exercise for 4 weeks, similarly the current study reported that maximum voluntary ventilation raised from 69.55 L to 104.78 L in the pelvic floor exercise training of 8 weeks [5]. Likewise, Yong, Lee & Lee (2017) concluded diaphragmatic breathing exercise enhance respiratory function [15]. In addition, the respiratory muscles may be anticipated to progress respiratory functions through increasing muscular strength and endurance through various forms of exercise [16].…”
Section: Resultssupporting
confidence: 78%
“…Han & Ha (2015) reported an increase in the maximum voluntary ventilation from 84.88 L to 112.62 L in reinforcement of the pelvic floor through pelvic floor exercise for 4 weeks, similarly the current study reported that maximum voluntary ventilation raised from 69.55 L to 104.78 L in the pelvic floor exercise training of 8 weeks [5]. Likewise, Yong, Lee & Lee (2017) concluded diaphragmatic breathing exercise enhance respiratory function [15]. In addition, the respiratory muscles may be anticipated to progress respiratory functions through increasing muscular strength and endurance through various forms of exercise [16].…”
Section: Resultssupporting
confidence: 78%
“…35 Such changes may be associated with improved cardiorespiratory fitness. [36][37][38][39][40][41] As a low METs (3.0) exercise, whether Tai Chi can produce the same level of cardiorespiratory benefits as high-impact aerobics exercise and its biological mechanisms need to be investigated and elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…17 The effects of deep abdominal muscle strengthening exercises on pulmonary function and the ability to balance in stroke patients were conducted to propose an exercise program for improving cardiovascular function and found that the experimental group showed a more effective significant difference than the control group. 18 The effects of diaphragm breathing exercise and feedback breathing exercise on respiratory function could also affect respiratory function. 19 Other studies also concluded that in male trainers that predominately engage in endurance compared to strengthrelated exercise, and appears to be unique differences in respiratory system characteristics.…”
Section: Discussionmentioning
confidence: 99%